Birth delivery assisted by nurse-midwife: perspectives and controversies - doi: 10.5020/18061230.2010.p380 - Selma Aparecida Lagrosa Garcia; Umberto Gazi Lippi; Sidney Antonio Lagrosa Garcia (Universidade de Fortaleza, 2012)
Objectives: To present the conflicts in birth deliveries assisted by nurse midwife and propose ways to minimize them. Methods: We researched the historical evolution of childbirth and the actions that were necessary for the training of professionals. Codes of Ethics of Nursing and Medicine, the current law, basic books of obstetrics and gynecology, articles from medical and nursing journals, with Lilacs and Medline as data sources; laic texts and others from non-governmental organizations (NGO) were surveyed. Conflicts were identified in birth deliveries by nurse midwife, for which we propose ways of acting. Results: The analysis of research material shows that the time of delivery, initially at home and afterwards in institutions, brought interventionism in this activity; that social and human aspects of birth and delivery were minimized and birth delivery changed into medical act. We found a strong link between the focus in humanization at child delivery and its assistance by nurses. Conclusions: We conclude that even with legal and ethical support the delivery care by nurse midwife is a source of conflict between the health team, particularly with regard to the limits of performance of the nurse and doctor. Such conflicts must be identified and discussed in the institutions and they should invest in teamwork and have clear protocols defining boundaries of responsibility.